ANALISIS FAKTOR KOMUNIKASI INTERPERSONAL GEMBALA DAN TIM PENGGEMBALAAN YANG EFEKTIF BAGI JEMAAT GBI GIHON RAYON 12 CABANG GRAND ELIT HOTEL PEKANBARU - Wong Pong Lan; Sussana Khatryn; Dony Chandra (POIMEN Jurnal Pastoral Konseling, 2021)
This research aims to determine the extent to which interpersonal communication factors have an important role in supporting a pastor in pastoring the congregation, where there are many problems that can arise due to ineffective communication, so that it can have an impact, either directly or indirectly on the growth of the faith of the congregation and the church. This research was motivated by the problem that the shepherds and the pastoral team were judged to be lacking in carrying out their pastoral functions at GBI GIHON Rayon 12 - Grand Elite Hotel Pekanbaru Branch. It was found that the focus on Sunday worship activities which emphasize communication is monologue. Meanwhile, pastoral conversational communication which is interpersonal dialogue is very limited. This is also felt by some members of the congregation, especially in worship services. That's why this study aims to examine and analyze the Interpersonal Communication of Pastors and Pastoral Teams for the Congregation of GBI GIHON Rayon 12 Grand Elite Hotel Pekanbaru Branch. The method used is quantitative with data collection through surveys with the development of explanatory and confirmatory research. The result of this research is that the tendency of effective interpersonal communication between Pastor and pastoral team for the GBI GIHON Rayon 12 congregation was found to be quite good, as well as each indicator. The most dominant indicator forming is a supportive communication indicator (X2). While the other influential is the worship session (X7).